การประชาสัมพันธ์การตลาดและโฆษณาที่นำเสนอภาพลักษณ์กับการตัดสินใจซื้อรถกระบะ - ศรัณรัชต์ ศักยะธัญวัฒน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
The purposes of this research is to survey the exposure of marketing public relations and television commercial projecting presenter image and buying decision of pick-up car and to test correlation of these variables. This study is a survey research that uses questionnaires as a method of data collecting from 400 samples that lived in Bangkok area. The results of the study show that samples expose to marketing public relations media in low level. However, the samples expose to product news and article, booth in motor show and sponsored program in fare level. The samples frequency expose to pickup car television commercial. The result of hypotheses testing is able to conclude that the exposure of marketing public relations media is low related to buying decision at significant level of 0.05. The exposure to television commercial projecting presenter image of pick-up car, "Me Tae Ruay" (Kot Jakaphan) is low related to buying decision at significant level of 0.05.